2020
DOI: 10.21203/rs.3.rs-38004/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Related Anxiety and Concerns Expressed by Pregnant and Postpartum Women- a Survey Among Obstetricians

Abstract: Abstract This paper from India describes anxieties that pregnant and postpartum women reported to obstetricians during the COVID-19 pandemic. Of the 118 obstetricians who responded to an online survey, most had been contacted for concerns about hospital visits (72.65%), methods of protection (60.17%), the safety of the infant (52.14%); anxieties related to social media messages (40.68%), contracting the infection (39.83%). Obstetricians felt the need for resources such … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Such results were expected in light of both the severity of the crisis caused by the pandemic, and the psychological vulnerability of pregnant women in general. They are also in line with the findings of other authors who identified higher levels of stress in pregnant women across the world (Berthelot et al, 2020, Corbett et al, 2020, Durankuş & Aksu, 2020, Kotabagi et al, 2020, Lebel et al, 2020, Masjoudi et al, 2020, Nanjundaswamy et al, 2020, Saadati et al, 2020, Saccone et al, 2020. Our study suggests that the intensity of fear of COVID-19 directly affects the stress response, but that there are also several psychological factors modulating this relationship.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Such results were expected in light of both the severity of the crisis caused by the pandemic, and the psychological vulnerability of pregnant women in general. They are also in line with the findings of other authors who identified higher levels of stress in pregnant women across the world (Berthelot et al, 2020, Corbett et al, 2020, Durankuş & Aksu, 2020, Kotabagi et al, 2020, Lebel et al, 2020, Masjoudi et al, 2020, Nanjundaswamy et al, 2020, Saadati et al, 2020, Saccone et al, 2020. Our study suggests that the intensity of fear of COVID-19 directly affects the stress response, but that there are also several psychological factors modulating this relationship.…”
Section: Discussionsupporting
confidence: 91%
“…Prolonged concern for own health and that of the loved ones, restriction of physical movement, social isolation, and the general sense of anxiety and uncertainty during the COVID-19 pandemic have all led to heightened levels of perceived stress and anxiety in the general population (Bao et al, 2020, Brooks et al, 2020, Wang et al, 2020. Furthermore, changes in the frequency and the routine of regular check-ups, lack of pregnancy-related peer-support networks, fear for the health and the life of the foetus, ban on the presence of birth support persons, and altered expectations related to perinatal and postnatal care have all been identified as important additional sources of stress for pregnant women, leading to a plausible assumption that the COVID-19-related anxiety might be particularly high in the population of pregnant women (Ali & Feroz, 2020, Fakari & Simbar, 2020, Matvienko-Sikar, 2020, Nanjundaswamy et al, 2020, Roy & Pless, 2020, Thapa et al, 2020, Zeng et al, 2020.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The General Health Questionnaire (GHQ) evaluate four dimensions of physical symptoms (1-7), anxiety and insomnia (8)(9)(10)(11)(12)(13)(14), social function (15)(16)(17)(18)(19)(20)(21), and depression (12). Higher scores represent worse general health.…”
Section: The General Health Questionnaire (Ghq)mentioning
confidence: 99%